2021
DOI: 10.3390/horticulturae7080224
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Chitosan and Chitosan Nanoparticles Improved Apple Fruit Resistance to Blue Mold, Upregulated Defense-Related Genes Expression, and Maintained Fruit Quality

Abstract: Blue rot disease caused by Penicillium expansum is one of the most widespread fungal diseases that affects apples worldwide. This work was to verify the effect of chitosan (2 and 4 g/L) and its nano-form (0.2 and 0.4 g/L) against blue rot disease on apples and their effect on the expression of six defense-related genes as well as fruit quality parameters. Regarding disease incidence, in most cases, chitosan NPs performed better as compared to their raw materials for both artificial and natural infections. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…(2022) indicated that CHNPs synthesized by ionic gelation had a mean size of 56 nm (Figure 1a). Similarly, several reports described the synthesis of CHNPs with a size of 50−100 nm using the same procedure (Abdel‐Rahman et al., 2021; Karimirad et al., 2019; Mohammadi et al., 2015a; Valizadeh et al., 2021). The ionic gelation method allowed the formation of CHNPs with spherical shapes (Figure 1b) (Gohari et al., 2021; Karimirad et al., 2018; Lustriane et al., 2018).…”
Section: Characteristics Of Chnpsmentioning
confidence: 96%
See 3 more Smart Citations
“…(2022) indicated that CHNPs synthesized by ionic gelation had a mean size of 56 nm (Figure 1a). Similarly, several reports described the synthesis of CHNPs with a size of 50−100 nm using the same procedure (Abdel‐Rahman et al., 2021; Karimirad et al., 2019; Mohammadi et al., 2015a; Valizadeh et al., 2021). The ionic gelation method allowed the formation of CHNPs with spherical shapes (Figure 1b) (Gohari et al., 2021; Karimirad et al., 2018; Lustriane et al., 2018).…”
Section: Characteristics Of Chnpsmentioning
confidence: 96%
“…Although some reports indicated that the ionic gelation technique formed spherical CHNPs (Abdel‐Rahman et al., 2021; Hesami et al., 2021; Karimirad et al., 2020; Karimirad et al., 2018; Saqib et al., 2019), the generated CHNPs showed in general amorphous shapes. Although the shape of the nanoparticles (NPs) is known to affect their properties (Ali et al., 2010; Wang, Shi, Zhu, et al., 2021), the shape of CHNPs was not considered in most studies.…”
Section: Characteristics Of Chnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro assay suggested that synthesized ChNPs in combination with T. asperellum was effective in suppressing mycelial growth of soil-borne fungal pathogens viz., Rhizoctonia solani, Fusarium oxysporum, and Sclerotium rolfsii. Abdel-Rahman et al [50] studied the efficacy of chitosan (Ch) (2 and 4 g/L) as well as ChNPs (0.2 and 0.4 g/L) against blue rot disease of apples caused by Penicillium expansum. They observed that ChNPs performed better than compared to their bulk counterpart for both natural and artificial infections.…”
Section: Application Of Chitosan Nanoparticles In Plant Health Manage...mentioning
confidence: 99%